Role of Leptin/Osteopontin Axis in the Function of Eosinophils in Allergic Rhinitis with Obesity - Liu, Wenlong; Zeng, Qingxiang; Chen, Yanqiu; Luo, Ren Zhong (Mediators of Inflammation, 2018)
Background. Allergic rhinitis (AR) is characterized by tissue and blood eosinophilia. Previous studies showed enhanced eosinophilia in allergic rhinitis patients with obesity, suggesting an association between obesity and eosinophilia. However, the interaction and mechanism between obesity and eosinophilia is still unclear. Methods. We recruited thirty AR children and 30 controls in this study. Expression of leptin and osteopontin (OPN) proteins in serum was detected, and correlation analysis with eosinophilia was performed. The effect of leptin or OPN on eosinophil apoptosis, adhesion, migration, and activation of eosinophil was examined. Ovalbumin-sensitized mice were established to prove the role of obesity on eosinophil regulation by leptin and OPN. Results. We found that upregulated serum and nasal leptin and OPN expression in AR were positively correlated with eosinophilia and eosinophil cationic protein levels. Leptin or OPN inhibited eosinophil apoptosis, demonstrated as inhibited DNA fragmentation and phosphatidylserine (PS) redistribution (P<0.05). Leptin and OPN promote expression of cluster of differentiation 18 (CD-18) and intercellular adhesion molecule 1 (ICAM-1) and inhibit expression of ICAM-1 and L-selectin by eosinophils, which contribute to the adhesion of eosinophils. Leptin and OPN mediated migration and activation of eosinophil through phosphatidylinositol-3-OH kinase (PI3K) pathway. Obese AR mice presented with more severe eosinophilia and symptoms compared with nonobese AR mice or control mice. Immunochemistry staining of leptin and OPN of nasal turbinate in obese AR mice was also stronger than those in nonobese AR mice or control mice. Anti-OPN, anti-leptin, and anti-α4 treatments reduce nasal eosinophilia inflammation and clinical symptoms in model mice. Conclusion. Our results suggested that in an obese state, upregulation of leptin and OPN regulates apoptosis, adhesion, migration, and activation of eosinophils, and this process may be mediated by the PI3K and anti-α4 pathways.